(107) electronic components for computers المكونات الإلكترونية لأجهزة الكمبيوتر - أ.د. نعيم أبو طالب (معهد التخطيط القومي, 2026)
تتناول هذه المذكرة تطور المكونات الإلكترونية وأجهزة التخزين في الحاسبات، حيث يستعرض الدكتور نعيم أبو طالب رحلة تطور الذاكرة من الحلول الميكانيكية والبطاقات المثقبة إلى الأنابيب الإلكترونية ثم الذاكرة المغناطيسية، مع التركيز على الوظائف الجوهرية لوحدات التخزين ومعايير تقييمها مثل السعة والسرعة والتكلفة والموثوقية، ويناقش المحتوى تقنيات حديثة (بمعايير وقتها) مثل "الكرايوترون" (Cryotron) والدوائر الدقيقة (Micro-Module Concept) التي كانت تمهد الطريق لتصغير حجم الحاسبات وزيادة كفاءتها بشكل ثوري، منتقلاً من الأجهزة الضخمة التي كانت تشغل مساحات هائلة إلى وحدات تخزين قادرة على حفظ ملايين المعلومات في حيز صغير.كما يسلط البحث الضوء على التطبيقات المستقبلية الطموحة لهذه الحاسبات في مجالات حيوية مثل التنبؤ بالطقس، والملاحة الفضائية، والترجمة الفورية للغات، بالإضافة إلى رقمنة الإدارة الجامعية، مؤكداً أن الوصول إلى عصر "الآلات المفكرة" يتوقف على تطوير ذاكرات ذات سعات هائلة وسرعات وصول فائقة تتجاوز الإمكانات التقليدية المتاحة آنذاك This paper examines the evolution of electronic components and storage devices in computers. Dr. Naeem Abu Taleb traces the development of memory from mechanical solutions and punched cards to electronic tubes and then magnetic memory, focusing on the essential functions of storage units and their evaluation criteria such as capacity, speed, cost, and reliability. The content discusses cutting-edge technologies (by the standards of their time) such as the cryotron and the micro-module concept, which paved the way for a revolutionary miniaturization and increased efficiency of computers, moving from bulky machines that occupied enormous spaces to storage units capable of storing millions of pieces of information in a small area. This paper examines the evolution of electronic components and storage devices in computers. Dr. Naeem Abu Taleb traces the development of memory from mechanical solutions and punched cards to electronic tubes and then magnetic memory, focusing on the essential functions of storage units and their evaluation criteria such as capacity, speed, cost, and reliability. The content discusses cutting-edge technologies (by the standards of their time) such as the cryotron and the micro-module concept, which paved the way for a revolutionary miniaturization and increased efficiency of computers, moving from bulky machines that occupied enormous spaces to storage units capable of storing millions of pieces of information in a small area. he research also highlights the ambitious future applications of these computers in vital fields such as weather forecasting, space navigation, and instant language translation, as well as the digitization of university administration, emphasizing that reaching the era of "thinking machines" depends on developing memories with enormous capacities and ultra-fast access speeds that exceed the conventional capabilities available at that time.